Antiphospholipid antibody-mediated interference with annexin-V anticoagulant activity - Rand, J. H.; Wu, X.-X. (Hämostaseologie, 2001)
The antiphospholipid (aPL) syndrome is a disorder in which vascular thrombosis and/or recurrent pregnancy losses occur together with serologic and coagulation evidence for antibodies directed against anionic phospholipid-protein complexes. Evidence has been developed for the idea that thrombosis in this syndrome may result from disruption of the binding of annexin-V to the phospholipids which line the placental and systemic vasculatures. We hypothesize that annexin-V, a protein known to have high affinity for anionic phospholipids, plays a thromboregulatory role at the vascular-blood interface by shielding anionic phospholipids from complexation with coagulation proteins in circulating blood. We propose that the thrombotic manifestations of the antiphospholipid syndrome are due to disruption of this annexin-V shield by antiphospholipid antibodies, thereby resulting in a net increase of thrombogenic phospholipids exposed to circulating blood. The accumulated data from tissue immunohistochemistry, trophoblast and endothelial cell culture studies, coagulation studies using noncellular phospholipids, and competition studies on artificial phospholipid bilayer are consistent with the hypothesis that the interference with the binding of annexin-V to anionic phospholipid surfaces plays an important role in the mechanism of thrombosis and in pregnancy loss in the antiphospholipid syndrome.
Keywords: Antiphospholipid syndrome; lupus anticoagulant; thrombosis; annexin-V